PENGARUH PENDIDIKAN ANTI-KORUPSI TERHADAP PERILAKU GENERASI MUDA DI INDONESIA - Muhamad Haidir Irsyadi; Kahpi Baiquni Arifani; Taufikurrahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Corruption is a significant issue that impacts various aspects of society, including economic, social, and political spheres, particularly in Indonesia. Anti-corruption education is viewed as a strategic solution to foster awareness, attitudes, and behaviors against corruption, especially among the younger generation, who are the future leaders of the nation. This study aims to examine the impact of anti-corruption education on the behaviors of young people and to evaluate effective pedagogical approaches for enhancing their awareness and understanding of the dangers of corruption. Previous studies have demonstrated that anti-corruption education improves students' awareness and understanding of principles such as honesty and integrity through both formal educational programs and applications within family settings. However, several challenges—such as a lack of governmental support, limited funding, and inadequate human resources—remain significant barriers to its implementation. This study also seeks to identify effective pedagogical methods that can be integrated into Indonesia's educational curriculum, including group discussions, simulations, and project-based learning. By employing interactive and participatory approaches, this research aims to provide strategic recommendations to enhance the effectiveness of anti-corruption education programs. The findings are expected to support the development of curricula focused on building the character and morality of Indonesia's younger generation, empowering them to become agents of change in eradicating corruption in the future.